Knowledge of National Health Insurance Scheme (NHIS) By Federal Civil Servants (FCSS) In Abuja Municipal Area Council (AMAC) Federal Capital Territory (FCT) - Agu, Michael Anene; Ngwu, Dorathy Chinwe (International Journal of Human Kinetics, Health and Education, 2023)
The study investigated the knowledge of NHIS by federal civil servant in Abuja municipal area council of federal capital territory of Nigeria. A cross-sectional survey designed was employed. The population consisted of 2015 federal civil servant. Whereas 400 were drawn as sample using stratified random sampling techniques. Researchers designed instrument was used for data collection. Three research questions were formulated to guide the study and were answered using mean percentage. Two null hypotheses were postulated and tested at .05 level of significance using ANOVA statistic. The findings revealed that FCSs had very high level of this dimension of NHIS, FCSs did not differ in their level of knowledge of NHIS according to gender and FCSs differ in their level of knowledge of NHIS according to age. Recommendations were made among which include that NHIS and Ministry of Health should still embark on some more intensified public enlightenment efforts in other to improve the knowledge of NHIS by FCSs to a very high level. Institutions of higher learning should include, (and vigorously teach) NHIS in school curricula to get students acquainted with NHIS before graduation in order to carry it on throughout life.